Composition and diversity of ants in dry relictual forests and vecinities in the region of Valle del Cauca, Colombia - ARMBRECHT, INGE; CHACÓN DE ULLOA, PATRICIA (Revista Colombiana de Entomología, 1997)
The ant assemblage was used for the first time in Colombia to study fragmentation in Tropical Dry Forest and to show the biological value of the remaining forests. Fourteen samplings were made in seven forest fragments and their surroundings, all of them located along Cauca river valley, in either of its margins and in a range of 220 km from north to south (Valle and Cauca departments). Each forest was visited twice. During each visit, both forest and matrix (the surroundings) were sampled in a four-100 m. transect system. Each transect included 40 stations, 160 tramps, and 40 litter samples. Additionally, eight hours of the manual collection were invested per visit. From a total of 3006 ant captures, 2093 were made inside forest and 913 in the matrix. From a total of 137 ant species, 123 were captured at least once inside a forest and 74 in a matrix. A highly significant correlation between all forests and their respective matrix richness was found. In all cases, more than 50% (until 89%) of the ant species were captured only in the forest (never in its matrix). Shannon diversity index inside the forest fragments fluctuated between 1.96 and 3.52. Shannon diversity indexes were significantly higher in the forest than in matrix in all cases except one. There was no statistical relationship between area and richness in this set of forests, probably because all of them are very small forest fragments fluctuating between 4-15 ha.